Legal Certificate of Electronic Certificate Based on Implementation Regulation of Law Number 11 of 2020 Concerning Work Creation - Alexander Dewa Gede Kyle Pranajaya Putra; Imam Koeswahyono; Hendrarto Hadisuryo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study entitled Legal Certainty of Electronic Certificates Based on the Implementing Regulations of Law Number 11 of 2020 concerning Job Creation with 2 (two) main problems, namely: (1) What is the strength of proof of electronic certificates in the event of a land dispute regarding dual certificates? (2) How about legal certainty. Electronic certificates in Indonesia before and after the enactment of Law Number 11 of 2020 concerning Job Creation? This research is a type of legal research with normative juridical research methods. Besides, this research uses a statutory approach and a conceptual approach. The results of this thesis research indicate that the land registration procedure to obtain an electronic certificate must refer to the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency no. 1 of 2021 concerning Electronic Certificates in accordance with the provisions of article 2 regarding the implementation of electronic land registration and also explained in article 6 for land that has not been registered and the replacement of certificates into electronic certificates for those that have been registered and clarified again in Government Regulation number 18 of 2021 concerning Management Rights , Land Rights, Flat Units and Land Registration, article 84 jo. Article 87 specifically regulates the implementation of land registration but for land that has not been registered and does not have a certificate, the registration process refers to Government Regulation number 24 of 1997 concerning Land Registration because only in the regulation it is regulated about land registration for the first time and systematic land registration until registration.